2014
DOI: 10.1111/pere.12052
|View full text |Cite
|
Sign up to set email alerts
|

Thin slices of infidelity: Determining whether observers can pick out cheaters from a video clip interaction and what tips them off

Abstract: The viability of using brief observations of behavior (thin slicing) to identify infidelity in romantic relationships was examined. Two studies supported the hypothesis that observers can accuratelsy identify people who are cheating on their romantic dating partner based on thin slices of observed behavior. In Study 1, raters were able to accurately identify people who were cheating on their romantic dating partner after viewing a short 3‐ to 4‐min video of the couple interacting. Study 2 replicated this findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Carrère and Gottman (1999) found that thin slice ratings of 3-min video clips of couples having a discussion from 6 years earlier could predict divorce rates. Similarly, in a study by Lambert et al (2014) raters could accurately identify which partner in a couple cheated on the other by watching 3-to 5-min clips of the couple's interactions. Jung (2016) also provides evidence that a team's work performance could be predicted by thin slice ratings of the quality of interactions between different team members based on 15 min of observation.…”
Section: The Thin Slices Procedures In the Context Of Instructional Rementioning
confidence: 99%
“…Carrère and Gottman (1999) found that thin slice ratings of 3-min video clips of couples having a discussion from 6 years earlier could predict divorce rates. Similarly, in a study by Lambert et al (2014) raters could accurately identify which partner in a couple cheated on the other by watching 3-to 5-min clips of the couple's interactions. Jung (2016) also provides evidence that a team's work performance could be predicted by thin slice ratings of the quality of interactions between different team members based on 15 min of observation.…”
Section: The Thin Slices Procedures In the Context Of Instructional Rementioning
confidence: 99%
“…Across four unique cultures (Azore Islands, Guinea-Bissau, Indonesia, and the U.S.), more attractive women (based on waist-to-hip ratio) were viewed as less faithful (Singh, 2004). Participants were able to correctly identify people who engaged in infidelity from a short video of a couple interacting, and trustworthiness and commitment mediated this relationship (Lambert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…These results may not generalize to children with lower ability levels, though we do not know of any thin slice study that has tested the impact of cognitive ability. Many thin slice studies rely on trained observers to judge the video clips (Lambert et al 2014) or untrained participants who are undergraduates (e.g. Oltmanns et al 2004) so variations in cognitive ability and the impact it has on thin slice judgments have not been examined.…”
Section: Limitationsmentioning
confidence: 99%